Validation and Factor Structure Analysis of the K-Dirty Dozen: A Korean Version of a Short-Form Measure of the Dark Triad - Cho, Hojin; Fengge, Li; Ma, Hong; Ock, Jisoo (Korean Journal of Industrial and Organizational Psychology, 2022)
The current study examined the construct validity and structural integrity of a Korean version of a short-form measure of the Dark Triad(K-Dirty Dozen). We recruited working adults in Korea to complete the K-Dirty Dozen, long-form measures of narcissism, Machiavellianism, and psychopathy, and the HEXACO personality traits. Then, we examined their intercorrelations to test the convergent and discriminant validity of the K-Dirty Dozen. Additionally, we conducted a series of confirmatory factor analyses to examine the internal factor structure of K-Dirty Dozen. Finally, we examined the criterion-related validity of K-Dirty Dozen by examining the correlations of its scores with counterproductive work behavior. We found results that generally provide support for the construct validity and structural integrity of K-Dirty Dozen. In addition to providing validity evidence for the K-Dirty Dozen, it is our hope that the current research will facilitate future research and discussions on the measurement of dark personality traits and their application to managing people in the workplace.